Simultaneous avant-gardes and horizontal art histories avant-gardes outside of the canonic narrations - Giunta, Andrea (2023)
Art history, particularly art history in Latin America, which is this author’s field of expertise, has been written as a story of centers and peripheries—centers that produce changes, discoveries and contributions to the languages of art and peripheries that reproduce (later) the discoveries of the centers. Particularly after WWII, it is not possible to sustain that scheme. Transformations in the language of art were produced at the same time or even on the peripheries earlier than in the center. To be more exact, the author prefers to talk of "simultaneous avant-gardes", a concept that aspires to recover the innovation and the spirit of transformation that Latin American avant-gardes demonstrate. This article offers a comparison between the concept of horizontal art history proposed by Piotr Piotrowski and a notion of simultaneous avant-gardes. It focuses on the 1960s–80s to explore practices that emerged basically beyond the centers and words that were used to name these practices, a new vocabulary to name what generally was termed "conceptualisms".
Keywords: Piotrowski, Piotr -- 1952-2015; Geschichte 1960-1990; Kunst; Konzeptualismus; Forschungsmethode; Avantgarde; Kunstgeschichte -- Fach; Lateinamerika